Analysis of Marketing Mix Implementation on Purchasing Decisions for Skintific Skincare Products (Survey of the Community in Jabodetabek) - Wahyudi, Muhammad Aria; Mulyono, Sri (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the impact of marketing mix implementation on purchasing decisions for Skintific Skincare Products among consumers in the Jabodetabek region. A quantitative research design was employed, surveying 200 respondents to gather insights into consumer preferences, brand perceptions, pricing influences, and marketing mix synergies. Results indicate that product quality and competitive pricing emerged as significant determinants of consumer satisfaction, brand loyalty, and purchase intention. Furthermore, correlations between marketing mix elements such as product quality, pricing, distribution channels, and promotional activities underscored their collective influence on consumer behavior and brand positioning. The findings offer strategic recommendations for Skintific to enhance market performance, sustain competitive advantage, and drive long-term success in the skincare industry.